On the boundary between Journalism and Literature: an approach to the “racconti-inchiesta” of Leonardo Sciascia - Serrano Puche, Javier (Estudios sobre el Mensaje Periodístico, 2012)
In the intellectual evolution of the Sicilian writer Leonardo Sciascia (1921-1989) there is an outstanding place for his dedication to journalism as a columnist in Italian newspapers and as an author of fictionalized stories. In these, Sciascia would investigate about a more or less recent historical episode that was still somewhat obscure or with an unclear meaning. Thus, with all the available documentation and using some narrative techniques, he would build up an investigation report with the aim of clarifying the facts. This paper describes the distinguishing features of the racconto-inchiesta as a genre of literary journalism and as a means for the Italian writer to restore the truth of the events through a hybrid writing between Journalism and Literature.